Cytotoxic effect of γ-sitosterol from Kejibeling (Strobilanthes crispus) and its mechanism of action towards c-myc gene expression and apoptotic pathway (Faculty of Medicine Universitas Indonesia, 2014)
Background: This study aimed to analyze the cytotoxicity effect of γ-sitosterol isolated from